PENINGKATAN MOTIVASI BELAJAR MELALUI BIMBINGAN KLASIKAL METODE PROBLEM-BASED LEARNING MEDIA KARTU MASALAH DI SMA NEGERI 6 SEMARANG - Muhammad Faizul Jismi; Anila Umriana; Ardiatma Rio Respati (Universitas Muria Kudus, 2025)
This study aims to examine the effectiveness of classical guidance services using the problem-based learning method supported by issue cards in enhancing students’ learning motivation. The novelty of this article lies in demonstrating how a student-centered learning approach can generate a positive impact on learners. The findings indicate that the classical guidance service based on problem-based learning with issue card media effectively increases the learning motivation of Grade XI K students at SMA Negeri 6 Semarang. Prior to the intervention, students’ motivation levels were generally in the moderate to low range; however, following the implementation, all students reached the high category, indicating a gradual improvement in interactive, motivational, and cognitive aspects.